A Review of Evidence on Gender Equality, Women’s Empowerment, and Food Systems - Njuki, Jemimah; Eissler, Sarah; Malapit, Hazel; Meinzen-Dick, Ruth S.; Bryan, Elizabeth; Quisumbing, Agnes R. (2021)
Jemimah Njuki, Sarah Eissler, Hazel Malapit, Ruth Meinzen-Dick, Elizabeth Bryan, and Agnes Quisumbing SPECIAL EVENT UNFSS Science Days Side Event: Gender Equality, Women’s Empowerment, and Food Systems Co-Organized by IFPRI and Self Employed Women’s Association (SEWA) JUL 6, 2021 - 07:00 AM TO 08:00 AM EDT